Public Perceptions of Citizen Science. (4th July 2017) - Lewandowski, Eva; Caldwell, Wendy; Elmquist, Dane; Oberhauser, Karen
Members of the public are the foundation and the backbone of citizen science, but much remains unknown about how the public views citizen science. We conducted a survey of public familiarity with, and perceptions of, citizen science. We found that less than half of respondents were familiar with the term "citizen science, " but over 70% were familiar with the concept by another name. Most respondents were more confident in hypothetical citizen science findings when professional scientists were involved to some degree, compared to situations in which only citizen scientists were involved. Confidence in citizen science findings tended to increase with age, despite the fact that self-confidence in respondents' own abilities to perform citizen science tasks decreased with age. Fewer than half of respondents (31–47%), and more men than women, were confident in their own ability to perform science process tasks, with the exception of collecting data (53% confident), and only slightly more predicted they would enjoy such activities. Based on our findings, we suggest ways in which leaders of citizen science projects can better promote recruitment, retention, and engagement on the part of volunteers and the public as a whole.